2019
DOI: 10.1108/ejm-07-2018-0468
|View full text |Cite
|
Sign up to set email alerts
|

Solving dissociative group effects using construal level theory

Abstract: Purpose Consumers usually respond favourably to ingroups but negatively to dissociative groups and products linked to dissociative groups, termed the dissociative group effect. Despite important implications for branding, advertising and celebrity endorsement, little is known about how to attenuate the effect. This paper aims to introduce a mechanism which attenuates the dissociative group effect by drawing on construal level theory. Design/methodology/approach An experimental approach was used which include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 77 publications
2
12
0
Order By: Relevance
“…Identity literature has largely ignored the potential influence of construal level on how consumers process and respond to information relevant to their identity. An exception is McGowan et al (2019), who show that consumers perceive themselves to be more similar to a dissociative group when in an abstract, relative to a concrete, mindset. The current research builds on and extends this finding, by showing that level of construal alters how prototypical a given group descriptor is perceived to be.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identity literature has largely ignored the potential influence of construal level on how consumers process and respond to information relevant to their identity. An exception is McGowan et al (2019), who show that consumers perceive themselves to be more similar to a dissociative group when in an abstract, relative to a concrete, mindset. The current research builds on and extends this finding, by showing that level of construal alters how prototypical a given group descriptor is perceived to be.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the level of construal have implications for categorization and personal perceptions (McGowan et al , 2019; Trope and Liberman, 2010), as an abstract mindset induces a similarity focus. To that effect, consumers in an abstract mindset focus on few important features that tie objects/events together, rather than emphasizing incidental or context-specific features.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Additionally, prior research has used CLT to explain various consumer perceptions, preferences, information processing and behaviors by linking construal levels to psychological distance (Adler and Sarstedt, 2021;Chiang et al, 2021;McGowan et al, 2019). For instance, drawing on CLT, McGowan et al (2019) explained how to attenuate the dissociative group effect by applying an experimental approach. Based on CLT, Chiang et al (2021) examined how the system characteristics of interactive augmentedreality technology (e.g.…”
Section: Engagement With Marketergenerated Contentmentioning
confidence: 99%
“…Additionally, prior research has used CLT to explain various consumer perceptions, preferences, information processing and behaviors by linking construal levels to psychological distance (Adler and Sarstedt, 2021; Chiang et al. , 2021; McGowan et al. , 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Research has consistently shown that consumers signal their social identity through consumption (Brough et al, 2016;Guzm an and Sierra, 2012;McGowan et al, 2019;Pinna, 2020). Consumers feel a stronger connection to brands that are associated with social groups to which they belong or aspire to belong (Escalas and Bettman, 2003) and a weaker connection to brands that are associated with groups to which they wish to avoid being associated with (McGowan et al, 2019;White and Dahl, 2007). In addition, consumers tend to stereotype brands/products and brand/product users (Bennett and Vijaygopal, 2018;Hess and Melnyk, 2016), which could potentially create a social threat to some groups.…”
Section: Introductionmentioning
confidence: 99%